Adapalene 0.1% and benzoyl peroxide 2.5% combination gel for the treatment of acne vulgaris. (August 2010) - Pariser, David
Combination therapy is a common approach in the treatment of acne vulgaris to simultaneously target the multiple pathogenic factors. The use of a topical retinoid in conjunction with an antimicrobial agent is a standard-of-care for most cases of acne. Recently, adapalene 0.1% and benzoyl peroxide 2.5% fixed-dose combination gel was approved for the treatment of acne vulgaris. Results from clinical trials provide robust evidence that this fixed-dose combination gel is significantly more efficacious than its corresponding monotherapies and has a mild tolerability profile similar to that of adapalene alone.